Contestation Of Public Discourse On The New Criminal Procedure Code (KUHAP) In The Digital Public Sphere - Mukhlish Muhammad Maududi (INJECT (Interdisciplinary Journal of Communication), 2026)
The enactment of Indonesia’s new Criminal Procedure Code (KUHAP) has generated widespread controversy in the digital public sphere, as reflected in polarized public sentiment and discursive contestation between the state and civil society. This study aims to examine how public sentiment is formed, circulated, and contested within the digital discourse surrounding the new KUHAP and its implications for the construction of legal legitimacy. Employing a qualitative descriptive approach, this study integrates social media–based sentiment analysis with critical discourse analysis. The data were derived from visualized public sentiment analytics produced by the DroneEmprit social media analytics platform. The findings reveal a predominance of negative and critical sentiments in the digital public sphere, centered on concerns regarding the potential erosion of human rights protections, expansion of law enforcement authority, and limited public participation in the legislative process. In contrast, state narratives emphasize legal certainty, law enforcement efficiency, and stability of the criminal justice system. The interaction between these competing narratives constitutes an arena of discursive contestation that exposes the polarization of legal legitimacy between state-centered procedural legitimacy and participatory legitimacy advocated by civil society. This study concludes that the digital public sphere functions as a strategic arena for negotiating legal legitimacy, in which the controversy over the new KUHAP reflects structural tensions between state authority and democratic demand.